2006
DOI: 10.1074/jbc.m603912200
|View full text |Cite
|
Sign up to set email alerts
|

CCL5-CCR5-mediated Apoptosis in T Cells

Abstract: CCL5 (RANTES (regulated on activation normal T cell expressed and secreted)) and its cognate receptor, CCR5, have been implicated in T cell activation. CCL5 binding to glycosaminoglycans (GAGs) on the cell surface or in extracellular matrix sequesters CCL5, thereby immobilizing CCL5 to provide the directional signal. In two CCR5-expressing human T cell lines, PM1.CCR5 and MOLT4.CCR5, and in human peripheral bloodderived T cells, micromolar concentrations of CCL5 induce apoptosis. CCL5-induced cell death involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 63 publications
1
26
0
Order By: Relevance
“…Although heparan sulfate is often considered the major GAG species that interacts with chemokines, both CS and dermatan sulfate (DS) also have submicromolar affinities for CCL5 (Mizumoto et al, 2013), establishing CS as a relevant target for investigation. In fact, CS has been shown to be important for the CCL5/CCR5-mediated induction of T cell apoptosis (Murooka et al, 2006), and for CCL5-induced monocyte arrest (von Hundelshausen et al, 2005). The sulfation pattern of CS and DS are also simpler than heparan sulfate (HS) and Hp, making them more convenient materials for the isolation of oligomers with defined structure.…”
Section: Introductionmentioning
confidence: 99%
“…Although heparan sulfate is often considered the major GAG species that interacts with chemokines, both CS and dermatan sulfate (DS) also have submicromolar affinities for CCL5 (Mizumoto et al, 2013), establishing CS as a relevant target for investigation. In fact, CS has been shown to be important for the CCL5/CCR5-mediated induction of T cell apoptosis (Murooka et al, 2006), and for CCL5-induced monocyte arrest (von Hundelshausen et al, 2005). The sulfation pattern of CS and DS are also simpler than heparan sulfate (HS) and Hp, making them more convenient materials for the isolation of oligomers with defined structure.…”
Section: Introductionmentioning
confidence: 99%
“…213 Upon binding to CCR5 on tumor infiltrating T lymphocytes, RANTES activates a CCR5-dependent apoptotic pathway that involves the release of cytochrome-c into the cytosol, activation of caspase-3 and caspase-9 pathways, and cleavage of poly ADPribose polymerase (PARP). 206,260,261 Hypoxia in the tumor microenvironment can induce strong release of RANTES, which promotes tumor migration. 262,263 In addition, RANTES in serum is associated with cancer clinical stage and tumor progression in several cancers (for review, see ref 264 264 ).…”
Section: Trail Rantes Rcas1mentioning
confidence: 99%
“…In addition, this locus has a close correlation with pulmonary infection. A previous study (16) reported that locus rs1799987 is a risk genotype that is related to the susceptibility of Chinese Han people to tuberculosis. However, it was mentioned in the paper of Carpenter et al (17) that locus rs1799987 is not related to the susceptibility to tuberculosis in adults in Peru, indicating that the locus has regional and racial differences.…”
Section: Discussionmentioning
confidence: 99%